Tax Planning for Income Tax Article 21 to Maximize Deductible Expenses on PT ABC - A A Bagus S I; I N Darmayasa; I W Purwanta (Journal of Applied Sciences in Accounting, Finance, and Tax, 2020)
This study aims to determine the appropriate tax planning application for Article 21 Income Tax for PT ABC so income tax income can be minimized according to applicable tax regulations. The type of data used in this study is quantitative and qualitative data. The data source is secondary. All data are collected by observation and documentation method. The data analysis technique is comparative descriptive analysis. Based on the results of the study it can be concluded that there are differences in income tax expense before and after the implementation of tax planning applied by PT ABC using a net basis method in the calculation of 21 employee income tax in 2018. Tax planning for PT ABC causes taxable income which is the basis for the imposition of corporate income tax to be smaller. Income tax payable before tax planning for 2018 amounted to Rp.232,687,569.00 to Rp. 230,071,387.00 after tax planning. This shows that there is tax savings of Rp.2,616,182.00. This research contributes to PT ABC by providing an alternative method of calculating income tax for 21 employees so as to minimize the tax burden which must be carried out PT ABC.